2012
DOI: 10.1093/aob/mcs227
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear phylogenetic analysis: SNPs, indels and SSRs deliver new insights into the relationships in the ‘true citrus fruit trees’ group (Citrinae, Rutaceae) and the origin of cultivated species

Abstract: Numerous molecular polymorphisms (SNPs and indels), which are potentially useful for the analysis of interspecific genetic structures, have been identified. The nuclear phylogenetic network for Citrus and its sexually compatible relatives was consistent with the geographical origins of these genera. The positive selection observed for a few genes will help further works to analyse the molecular basis of the variability of the associated traits. This study presents new insights into the origin of C. sinensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
137
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(174 citation statements)
references
References 79 publications
27
137
2
8
Order By: Relevance
“…Poncirus and Microcitrus were quite distant from Citrus (high bootstrap values), while Fortunella was more closely related. This analysis supported the phylogenetic relationships in the Citrinae established using other markers (Nicolosi et al, 2000;Garcia-Lor et al, 2013a, 2013bPenjor et al, 2013;Ramadugu et al, 2013) but did not reveal the distinct phylogenetic cluster of citron and Microcitrus established using the complete chloroplast DNA of 34 species (Carbonell-Caballero et al, 2015).…”
Section: Phylogenetic Analysismentioning
confidence: 54%
See 1 more Smart Citation
“…Poncirus and Microcitrus were quite distant from Citrus (high bootstrap values), while Fortunella was more closely related. This analysis supported the phylogenetic relationships in the Citrinae established using other markers (Nicolosi et al, 2000;Garcia-Lor et al, 2013a, 2013bPenjor et al, 2013;Ramadugu et al, 2013) but did not reveal the distinct phylogenetic cluster of citron and Microcitrus established using the complete chloroplast DNA of 34 species (Carbonell-Caballero et al, 2015).…”
Section: Phylogenetic Analysismentioning
confidence: 54%
“…Sweet orange (C. sinensis) is considered a complex hybrid involving mandarin (providing the predominant genetic material) and pummelo (Garcia-Lor et al, 2013b;Xu et al, 2013;Wu et al, 2014), and the allelic composition of the Ruby locus (r TATA and r DEL2 ) confirmed this. We have been unable to detect any expression of Ruby in different tissues of common varieties of sweet orange (Butelli et al, 2012), consistent with the complete absence of anthocyanin pigmentation.…”
Section: Ruby In Citrus Hybridsmentioning
confidence: 93%
“…In Citrus, recently, a rough draft of the genome was completed using the haploid Clementine mandarin and the doubled haploid sweet orange (Ollitrault et al, 2012;Xu et al, 2013). This genomic information has also been applied for the development of DNA markers, genetic analysis, and the production of new cultivars (Ahmad et al, 2013;Cuenca et al, 2013;Garcia-Lor et al, 2013). Our doubled haploid pummelo will also be utilized as alternative material for these genetic and breeding studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Luro et al (1995) found high polymorphism among mandarin genotypes using microsatellite (SSR) markers. Additionally, mandarins contained a large number of genetic polymorphisms in many studies that were performed to clarify the diversity and taxonomy of Citrus (Nicolosi et al, 2000;Luro et al, 2001;Barkley et al, 2006;Ollitrault et al, 2012;Garcia-Lor et al, 2013). Simsek et al (2011) reported that mandarins have high allelic diversity in iron chlorosis tolerance genes (Fe-S assembly protein and irt1).…”
Section: Discussionmentioning
confidence: 99%